Keteladanan Guru Pendidikan Agama Islam dalam Internalisasi Nilai-Nilai Akhlakul Karimah pada Siswa - Harmita, Dwi; Nurbika, Deka; Asiyah, Asiyah (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study was to describe the role model of PAI teachers in internalizing the moral values ​​of students at SMPN 7 Bengkulu City. This type of research is included in field research which is a case study with a descriptive qualitative approach, in which there are attempts to describe, record, analyze and interpret conditions that are currently happening or exist. The subjects of this study were school principals, PAI teachers and students. The results of the study, appreciation of the internalization of moral values ​​in schools, teachers apply several stages that represent the process of internalization, namely the value transformation stage, the value transaction stage, and the value internalization stage, where the three stages are used to educate students' morals to have good behavior. In conclusion, Islamic Religious Education (PAI) lessons at SMPN 7 Bengkulu City are not only focused on in the classroom, but also carried out outside the classroom, such as the implementation of worship practices in the prayer room, recitation of the Qur'an in class, and worship practices. other. Not only that, students are fostered to get used to speaking politely to teachers and fellow friends, maintaining attitudes and behavior, getting used to dressing well (covering the genitals), and keeping the school environment clean and tidy so that it looks beautiful. The habituation aims so that students can appreciate and practice moral values. Keywords: Akhlakul Karimah, Internalization of Values, Exemplary